Pemanfaatan Sumber Belajar Melalui Internet Dalam Rangka Peningkatan Motivasi Belajar Siswa SMK - Hardiansyah, Hardiansyah; Suciyati, Suciyati (STKIP Taman Siswa Bima, 2024)
The study aimed at examining (1) the extend of the improvement of students’ learning motivation through the use of internet learning sources on vocational competencies lesson of Computer Network Engineering (TKJ); (2) whether the use of learning sources through internet obtain positive response from the students on vocational competencies lesson of Computer Network Engineering (TKJ); and (3) the effectiveness of the used of learning sources through internet at SMKN 1 in Bima on vocational competencies lesson of Computer Network Engineering (TKJ). The study was a classroom action research which consisted of two cycles that each of the cycle was conducted in three sessions. The results of the study revealed that (1) Students’ learning motivation was improved in utilizing learning sources through internet on vocational competencies lesson of Computer Network Engineering (TKJ); (2) the utilization of learning sources through internet on vocational competencies lesson of Computer Network Engineering (TKJ) obtained positive response from the students; and (3) based on the result of learning outcomes which was improved on vocational competencies lesson of Computer Network Engineering (TKJ), it was confirmed that the utilization of learning sources through internet was effective to be in grade X of TKJ 2 at SMKN 1 in Bima ABSTRAK Tujuan penelitian ini adalah: (1) untuk mengetahui seberapa besar peningkatan motivasi belajar siswa melalui pemanfaatan sumber belajar internet pada mata pelajaran kompetensi kejuruan TKJ; (2) untuk mengetahui respon positif siswa terhadap pemanfaatan sumber belajar melalui internet pada mata pelajaran kompetensi kejuruan TKJ; dan (3) untuk mengetahui efektifitas pemanfaatan sumber belajar melalui internet terhadap peningkatan hasil belajar siswa di SMKN 1 Bima pada mata pelajaran kompetensi kejuruan TKJ. Metode penelitian ini adalah penelitian tindakan kelas (PTK), terdiri dari dua siklus, dimana setiap siklus dilaksanakan selama tiga kali pertemuan. Hasil penelitian menunjukkan bahwa (1) motivasi belajar siswa meningkat dalam memanfaatkan sumber belajar melalui internet pada mata pelajaran kompetensi kejuruan TKJ, (2) Pemanfaatan sumber belajar melalui internet pada mata pelajaran kompetensi kejuruan TKJ mendapat respon positif dari siswa, dan (3) berdasarkan nilai hasil belajar siswa yang meningkat 90% pada mata pelajaran kompetensi kejuruan TKJ, maka pemanfaatan sumber belajar melalui internet efektif digunakan di kelas X TKJ 2 SMKN 1 Bima.